2020
DOI: 10.1111/ans.15650
|View full text |Cite
|
Sign up to set email alerts
|

Process measure aimed at reducing time to haemorrhage control: outcomes associated with Code Crimson activation in exsanguinating truncal trauma

Abstract: BackgroundMajor trauma activation is a process that mobilizes personnel and resources required to care for severely injured patients. Exsanguinating truncal trauma patients require an additional response beyond major trauma activation aimed at expediting haemorrhage control. To address this requirement, ‘Code Crimson’ (CC) activation was developed. Our aim was to examine the performance of CC activation as a process measure in the identification and management of patients with exsanguinating truncal trauma.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Code Crimson, for example, is a pre‐hospital and ED protocol used across Australasia, though not in our centre. Based on the haemodynamic parameters of patients, pre‐hospital or the ED team can activate a Code Crimson 11 . Once a Code Crimson is activated, the consultant surgeon and anaesthetist are notified to attend ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Code Crimson, for example, is a pre‐hospital and ED protocol used across Australasia, though not in our centre. Based on the haemodynamic parameters of patients, pre‐hospital or the ED team can activate a Code Crimson 11 . Once a Code Crimson is activated, the consultant surgeon and anaesthetist are notified to attend ED.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the haemodynamic parameters of patients, pre-hospital or the ED team can activate a Code Crimson. 11 Once a Code Crimson is activated, the consultant surgeon and anaesthetist are notified to attend ED. This process allows for senior decision-makers to be present at the assessment and initial management of unstable patients, allowing for optimal planning for definitive management.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there was no reduction in pre‐hospital time, or time taken from hospital arrival until beginning the haemorrhage control laparotomy. This was despite introducing the ‘code crimson’ call in 2015, which aims hasten decision making and reduce time delays to achieve haemorrhage control, with pre‐hospital identification of critically unstable patients and involving senior staff members early 17 . We believe this reflects minimal delay in the first part of the study as a baseline, which was difficult to improve upon.…”
Section: Discussionmentioning
confidence: 99%
“…in Australia and New Zealand. [1][2][3] PHIs in Singapore have yet to initiate this form of step-up trauma activation. Code Crimson activation mobilises additional personnel and resources who are specifically required for decision-making, above those that are required for most major trauma activations.…”
mentioning
confidence: 99%
“…Moreover, Code Crimson at Westmead Hospital in Sydney, Australia significantly reduced the median time from ED to OT to 23 minutes versus 59 minutes in patients with major haemorrhage in whom the code was not activated. 1 In 2018, Critical Haemorrhage to Operation Room Patient (CHOP) protocol was implemented by the Department of General Surgery at Khoo Teck Puat Hospital in Singapore, with a goal of bringing a severely injured patient rapidly to definitive care within 90 minutes. Analysis of the first 10 cases of CHOP protocol activation reported an average time of 73 minutes from the time of patient's arrival at ED to transfer to OT or IR suite.…”
mentioning
confidence: 99%